Antioxidant Activity of n-Hexane Subfraction of Buas-Buas Leaf (Premna serratifolia L.) by DPPH Method - Darin Iftinan; Isnindar Isnindar; Sri Luliana (Biology, Medicine, & Natural Product Chemistry, 2026)
Buas-buas (Premna serratifolia L.) is a plant traditionally used as medicine and widely grown in West Kalimantan with various species. There are many benefits of buas-buas plants as medicine, one of which is as an antioxidant. The purpose of this study was to determine the percent inhibition value that describes the antioxidant activity of ethanol extract, n-hexane fraction, and n-hexane subfraction of buas-buas leaves. The n-hexane fraction was obtained by liquid-liquid extraction with separatory funnel from ethanol extract and the fraction was isolated by column chromatography. The antioxidant activity of the ethanol extract, n-hexane fraction, and subfractions C1, C2, C3, D123, and E3F123 was assessed using DPPH (2,2-Diphenyl-1-Picrylhydrazyl). The results showed that ethanol extract, n-hexane fraction, and subfractions C1, C2, C3, D123, and E3F123, had antioxidant activity with percent inhibition values of 57.946; 53.078; 52.652; 48.706; 49.745; 50.490; and 50.639%, respectively, which indicated that each sample had good antioxidant activity, except for subfractions C2 and C3.